Development of Textile Nanocomposites With Thermal Energy Storage Capability - Önder, Emel; SARIER, NİHAL (Natl Inst Science Communication-Niscair, 2021)
In this study, textile-based composites with dynamic heat storage capability have been designed and developed, in addition to their existing passive insulation capacity. First, poly(acrylonitrile) (PAN) shell and poly(ethylene glycol) (PEG1000 or PEG1500) cores are produced by coaxial electrospinning. Then, these are incorporated into felt based composite structures, which demonstrate enhanced thermal properties as well as buffering function against temperature changes in the environment. The thermal energy absorption and release capacities of the felt composites including PANPEG1000 or PAN-PEG1500 nanowebs are measured as high as 81 Jg(-1) between 33 degrees C and 46 degrees C, and 48 Jg(-1) between 46 degrees C and 54 degrees C respectively. Felt composites, combined with PAN-PEG nanowebs offer forthcoming production applications in the field of dynamic thermal management in various industries.
Keywords: Differential Scanning Calorimetry; Dynamic Mechanical Analysis; Electrospinning; Nanocomposite; Phase Change Materials; Poly(Acrylonitrile)